2017
DOI: 10.4132/jptm.2016.10.03
|View full text |Cite
|
Sign up to set email alerts
|

KRAS Mutation Test in Korean Patients with Colorectal Carcinomas: A Methodological Comparison between Sanger Sequencing and a Real-Time PCR-Based Assay

Abstract: BackgroundMutations in the KRAS gene have been identified in approximately 50% of colorectal cancers (CRCs). KRAS mutations are well established biomarkers in anti–epidermal growth factor receptor therapy. Therefore, assessment of KRAS mutations is needed in CRC patients to ensure appropriate treatment.MethodsWe compared the analytical performance of the cobas test to Sanger sequencing in 264 CRC cases. In addition, discordant specimens were evaluated by 454 pyrosequencing.ResultsKRAS mutations for codons 12/1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…In a study researching KRAS mutation frequencies in Caucasian colorectal cancer patients, KRAS mutations were found in 38.3% [ 65 ]. A study of colorectal cancer patients in South Korea reported that KRAS mutations were found in 45.9% [ 66 ]. Meanwhile, the KRAS mutation rate of primary cancer was higher in this study compared to 30%–40% in previous studies [ 65 , 66 ], which seems to be because the study was conducted on BM patients.…”
Section: Metastatic Colon Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In a study researching KRAS mutation frequencies in Caucasian colorectal cancer patients, KRAS mutations were found in 38.3% [ 65 ]. A study of colorectal cancer patients in South Korea reported that KRAS mutations were found in 45.9% [ 66 ]. Meanwhile, the KRAS mutation rate of primary cancer was higher in this study compared to 30%–40% in previous studies [ 65 , 66 ], which seems to be because the study was conducted on BM patients.…”
Section: Metastatic Colon Cancermentioning
confidence: 99%
“…A study of colorectal cancer patients in South Korea reported that KRAS mutations were found in 45.9% [ 66 ]. Meanwhile, the KRAS mutation rate of primary cancer was higher in this study compared to 30%–40% in previous studies [ 65 , 66 ], which seems to be because the study was conducted on BM patients. RAS mutation analysis in colorectal cancer patients reported that RAS mutations affect the increased incidence of lung, bone and BM [ 67 ].…”
Section: Metastatic Colon Cancermentioning
confidence: 99%